Positive electrode additive and preparation method thereof, positive electrode plate and preparation method thereof, and lithium ion battery

By using the positive electrode additive with a core-shell structure in the positive electrode sheet of the lithium-ion battery, the problem of uneven electrolyte infiltration in the positive electrode active material composite system is solved, which significantly improves the battery's circulation and storage performance, and reduces the liquid injection coefficient.

CN119552388APending Publication Date: 2025-03-04PHYLION BATTERY (CHUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411741681.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The positive electrode active material composite system in lithium-ion batteries has problems such as uneven electrolyte infiltration, resulting in uneven charging and discharging interfaces, low Coulomb efficiency, low actual capacity performance, and cycle deterioration.

Method used

The positive electrode additive with a core-shell structure is used to obtain polymer organic acid particles and use an esterification reaction to form an ester shell to form a core and a lipid shell with high liquid absorption function, which is used to enhance the wetting effect of the positive electrode sheet.

Benefits of technology

Significantly improve the wetting effect of the positive electrode sheet, improve the circulation and storage performance of the battery, improve the uniformity of the charging and discharge interface, and reduce the liquid injection coefficient of the lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552388A_ABST
    Figure CN119552388A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode additive and a preparation method thereof, a positive electrode plate and a preparation method thereof, and a lithium ion battery. The positive electrode additive with a core-shell structure is obtained by reacting the surface layers of the high-molecular organic acid particles through esterification reaction to form an ester shell. The positive electrode additive can form a polymer network in the positive electrode plate, and the polymer has the physical characteristic of high swelling, can absorb electrolyte in a rich liquid state and can release the electrolyte in a poor liquid state, and has the main effects of remarkably improving the infiltration effect of the positive electrode plate, improving the battery capacity, improving the interface and improving the cycle performance. And moreover, the performance is improved, and meanwhile, the liquid injection coefficient of the lithium ion battery can be remarkably reduced. The positive pole piece and the lithium ion battery both use the positive pole additive, so that the positive pole piece and the lithium ion battery also have relatively good performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode additive and a preparation method thereof, a positive electrode sheet and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries often have problems such as uneven electrolyte infiltration, resulting in uneven charge and discharge interfaces, low coulombic efficiency, low actual capacity, and cycle degradation, which lead to poor battery performance. In particular, the above problems are more obvious in positive electrode systems composed of two or more positive electrode active materials due to large differences in specific surface area and particle size.

[0003] In view of this, this application is hereby filed. Summary of the invention

[0004] The purpose of the present application is to provide a positive electrode additive and a preparation method thereof, a positive electrode plate and a preparation method thereof, and a lithium-ion battery. The positive electrode additive proposed in the present application can effectively enhance the wetting effect of the plate and improve the battery performance.

[0005] This application is implemented as follows:

[0006] In a first aspect, the present application provides a method for preparing a positive electrode additive for preparing a positive electrode additive for a lithium ion battery. The method for preparing the positive electrode additive comprises:

[0007] Obtaining high molecular weight organic acid particles;

[0008] The surface layer of the polymer organic acid particles is reacted by esterification reaction to form an ester shell, so as to obtain a positive electrode additive with a core-shell structure.

[0009] In an optional embodiment, the step of obtaining high molecular organic acid particles includes:

[0010] Using an initial organic acid to obtain a high molecular weight organic acid through a polymerization reaction;

[0011] The high molecular weight organic acid is granulated to obtain high molecular weight organic acid particles.

[0012] In an optional embodiment, the particle size of the polymer organic acid particles is 0.001 to 3 μm.

[0013] In an optional embodiment, the structural formula of the initial organic acid is The structural formula of high molecular weight organic acid is Wherein, R1 is an unsaturated alkenyl or alkynyl group, and the number of carbon atoms is 2 to 5.

[0014] In an optional embodiment, the step of using an esterification reaction to react the surface layer of the polymer organic acid particles to form an ester shell to obtain a positive electrode additive with a core-shell structure includes:

[0015] The polymer organic acid particles are placed in an alcohol solution, and the surface layer of the polymer organic acid particles is reacted to form an ester shell under the catalysis of an inorganic catalyst to obtain a positive electrode additive with a core-shell structure.

[0016] In an optional embodiment, the structural formula of the alcohol solution is Wherein, R2 is a substituted or unsubstituted alkyl group containing 1 to 5 carbon atoms, or a substituted or unsubstituted alkenyl group containing 2 to 5 carbon atoms, or a functional group containing 5 carbon atoms and the substituent is F or contains F.

[0017] In a second aspect, the present application provides a positive electrode additive, which is prepared by the preparation method of the positive electrode additive of any one of the aforementioned embodiments.

[0018] In a third aspect, the present application provides a method for preparing a positive electrode sheet, comprising:

[0019] Obtaining a positive electrode slurry containing a positive electrode active material;

[0020] Mixing the positive electrode slurry with the positive electrode additive of the above embodiment to obtain a composite positive electrode slurry;

[0021] The composite positive electrode slurry is coated on the current collector to obtain a positive electrode sheet.

[0022] In an optional embodiment, the positive electrode active material is selected from at least one of lithium manganese oxide, lithium iron manganese phosphate and nickel-cobalt-manganese ternary materials.

[0023] In an optional embodiment, the step of obtaining a positive electrode slurry containing a positive electrode active material comprises:

[0024] Mixing polyvinylidene fluoride and N-methylpyrrolidone, and stirring evenly to obtain a glue solution;

[0025] Disperse the conductive agent evenly in the glue solution;

[0026] The positive electrode active material is uniformly dispersed in the glue solution to obtain a positive electrode slurry.

[0027] In an optional embodiment, the process conditions for stirring to obtain the glue solution include: a revolution speed of 30 to 50 rpm, a rotation speed of 2000 to 4000 rpm, and a duration of 1 to 3 hours;

[0028] The process conditions for dispersing the conductive agent in the glue solution include: a revolution speed of 30 to 50 rpm, a rotation speed of 2000 to 4000 rpm, and a duration of 0.5 to 2 hours;

[0029] The process conditions for dispersing the positive electrode active material with the glue solution include: a revolution speed of 30 to 50 rpm, a rotation speed of 2000 to 4000 rpm, and a duration of 3 to 5 hours.

[0030] In an optional embodiment, the positive electrode slurry and the positive electrode additive are mixed at a revolution speed of 30 to 50 rpm.

[0031] In an optional embodiment, the amount of the positive electrode additive used satisfies the formula: 0.001≤x / (η*a)≤300; wherein x is the mass fraction of the positive electrode additive to the total amount of the positive electrode material on the current collector, η is the porosity of the positive electrode plate, and a is the lithium salt concentration in the electrolyte of the lithium-ion battery used in the positive electrode plate, expressed in mol / L.

[0032] In a fourth aspect, the present application provides a positive electrode sheet, which is prepared by the method for preparing a positive electrode sheet of any one of the aforementioned embodiments.

[0033] In a fifth aspect, the present application provides a lithium-ion battery, comprising the positive electrode sheet of the aforementioned embodiment.

[0034] This application has the following beneficial effects:

[0035] The preparation method of the positive electrode additive provided in the embodiment of the present application includes: obtaining polymer organic acid particles; using an esterification reaction to react the surface of the polymer organic acid particles to form an ester shell to obtain a positive electrode additive with a core-shell structure. In the positive electrode additive with a core-shell structure, the core of the polymer organic acid can play a better liquid absorption function, and the lipid shell has a better liquid retention function. Used as a functional additive, the positive electrode additive can form a polymer network in the positive electrode plate. The polymer has a highly swellable physical property. It absorbs electrolyte in a liquid-rich state and releases electrolyte in a liquid-poor state. Its main function is to significantly improve the wetting effect of the positive electrode plate, improve the battery capacity, improve the interface, and improve the cycle performance. Moreover, while improving the performance, it can significantly reduce the injection coefficient of the lithium-ion battery.

[0036] The positive electrode additive provided in the embodiment of the present application is prepared by the above preparation method. The positive electrode plate and its preparation method, and lithium ion battery provided in the embodiment of the present application all use the above positive electrode additive, so the obtained positive electrode plate and lithium ion battery have better performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 This is a flow chart of a method for preparing a positive electrode additive in one embodiment of the present application;

[0039] Figure 2 This is a microscopic view of polymer organic acid particles in one embodiment of the present application;

[0040] Figure 3 This is a flow chart of a method for preparing a positive electrode plate in one embodiment of the present application. DETAILED DESCRIPTION

[0041] As mentioned above, current lithium-ion batteries are prone to problems such as uneven electrolyte infiltration, resulting in uneven charge and discharge interfaces, low coulombic efficiency, low actual capacity utilization, and cycle degradation. These problems are more common in positive electrode systems composed of two or more positive electrode active materials. To this end, an embodiment of the present application provides a positive electrode additive and a preparation method thereof, which significantly improves the wetting performance of the positive electrode sheet by adding a positive electrode additive with a core-shell structure to the positive electrode sheet, thereby improving the cycle performance of the battery.

[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0043] Figure 1 Flow chart of a method for preparing a positive electrode additive in one embodiment of the present application. Figure 1 As shown, the preparation method of the positive electrode additive provided in the embodiment of the present application is used to prepare the positive electrode additive of the lithium ion battery, and the preparation method comprises the following steps:

[0044] Step S10, obtaining polymer organic acid particles.

[0045] In the embodiment of the present application, step S10 may specifically include:

[0046] Step S11, using the initial organic acid to obtain a high molecular weight organic acid through a polymerization reaction;

[0047] Step S12, granulating the polymer organic acid to obtain polymer organic acid particles.

[0048] Optionally, the structural formula of the initial organic acid is The structural formula of the high molecular weight organic acid obtained by polymerization is Wherein, R1 is an unsaturated alkenyl or alkynyl group, and the number of carbon atoms is 2 to 5. In this embodiment, n is greater than or equal to 2. In the subsequent manufacturing process, the polymer organic acid is used to form the core of the core-shell structure particle, and the polymer organic acid as the core has a better liquid absorption function.

[0049] The polymerization reaction to generate high molecular weight organic acid can be carried out under different initiation modes (such as thermal initiation, photoinitiation, electrical initiation, etc.).

[0050] Granulation can be achieved by a granulator. Optionally, the particle size of the high molecular organic acid particles is 0.001 to 3 μm, and the high molecular organic acid particles can be spherical particles. Figure 2 This is a microscopic view of polymer organic acid particles in one embodiment of the present application.

[0051] Step S20, using an esterification reaction to react the surface layer of the high molecular organic acid particles to form an ester shell, so as to obtain a positive electrode additive with a core-shell structure.

[0052] It should be understood that the reaction (esterification) of the macromolecular organic acid with the alcohol can generate lipid substances and water. In the present application embodiment, only the surface layer of the macromolecular organic acid particles participates in the esterification reaction, while the central part does not participate in the esterification reaction. The central part of the macromolecular organic acid particles that does not participate in the esterification reaction forms the core in the core-shell structure, while the outer part that participates in the esterification reaction forms the lipid shell of the core-shell structure.

[0053] In an optional embodiment, the initial organic acid is acrylic acid, the high molecular weight organic acid is a high molecular weight polymer of acrylic acid, and the lipid shell is a high molecular weight polymer of acrylate.

[0054] Optionally, step S20 is specifically implemented in the following manner:

[0055] The polymer organic acid particles are placed in an alcohol solution, and the surface layer of the polymer organic acid particles is reacted to form an ester shell under the catalysis of an inorganic catalyst to obtain a positive electrode additive with a core-shell structure. Optionally, the structural formula of the alcohol solution is Wherein, R2 is a substituted or unsubstituted alkyl group containing 1 to 5 carbon atoms, or a substituted or unsubstituted alkenyl group containing 2 to 5 carbon atoms, or a functional group containing 5 carbon atoms and the substituent is F or F. The substituent in R2 is F or F-containing functional group, and its main function is to improve oxidation resistance, broaden the electrochemical window, and enhance the matching of the system. The positive electrode additive has polar groups (-COOH, -F, -P, -N, etc.) with high affinity for the electrolyte, which can significantly improve the wetting effect of the positive electrode sheet.

[0056] Appropriate light and heat conditions are conducive to the esterification reaction. The reaction condition parameters should be reasonably selected according to the required product form (such as the required lipid shell thickness).

[0057] Optionally, after the esterification reaction is completed, the obtained product can be washed and dried to ensure the cleanliness of the positive electrode additive. Specifically, the product after the esterification reaction can be dispersed in pure water and then evaporated and crystallized. Optionally, the positive electrode additive after water washing can also be dispersed in ethanol and then evaporated and crystallized to finally obtain a positive electrode additive with a core-shell structure with high cleanliness.

[0058] In the positive electrode additive obtained by the preparation method provided in the embodiment of the present application, the core mainly plays a high liquid absorption function, and the lipid shell mainly plays a liquid retention function. The positive electrode additive provided in the embodiment of the present application is used as a functional additive, which can form a polymer network in the positive electrode plate. The polymer has a highly swellable physical property, absorbs electrolyte in a liquid-rich state, and releases electrolyte in a liquid-poor state. It can significantly improve the wetting effect of the positive electrode plate, improve the battery capacity, improve the interface, and improve the cycle performance. And while improving the performance, it can significantly reduce the injection coefficient of the lithium-ion battery.

[0059] The positive electrode additive provided in the embodiment of the present application is prepared by the above-mentioned preparation method of the positive electrode additive.

[0060] Figure 3 Flow chart of a method for preparing a positive electrode sheet in one embodiment of the present application. Figure 3 As shown, the method for preparing the positive electrode sheet provided in the embodiment of the present application comprises the following steps:

[0061] Step S100, obtaining positive electrode slurry containing positive electrode active materials.

[0062] In an optional embodiment of the present application, the positive electrode active material is selected from at least one of lithium manganese oxide, lithium iron manganese phosphate and nickel cobalt manganese ternary materials, that is, the positive electrode active material can be one of lithium manganese oxide, lithium iron manganese phosphate and nickel cobalt manganese ternary materials, or it can be a mixture of two of the three or even a mixture of the three.

[0063] Optionally, step S100 includes:

[0064] Step S110 , mixing polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP), and stirring them evenly to obtain a glue solution.

[0065] Step S120, uniformly dispersing the conductive agent in the glue solution;

[0066] Step S130, uniformly dispersing the positive electrode active material in the glue solution to obtain a positive electrode slurry.

[0067] In the embodiment of the present application, PVDF can be used as a binder in the positive electrode material, and NMP can be used as an organic solvent. The two can be mixed to obtain a glue with suitable viscosity. It can be understood that if the viscosity of the glue is too high, it will make it difficult for the conductive agent, positive electrode active material and positive electrode additive to be evenly dispersed in the glue, while if the viscosity of the glue is too low, it will be unfavorable for the subsequent coating and the process of making the positive electrode sheet.

[0068] Optionally, the process conditions for stirring to obtain the glue solution include: an orbital speed of 30 to 50 rpm, a rotation speed of 2000 to 4000 rpm, and a duration of 1 to 3 hours; for example, an orbital speed of 40 rpm, a rotation speed of 2700 rpm, and a duration of 2 hours.

[0069] Optionally, the process conditions for dispersing the conductive agent in the glue solution include: an orbital speed of 30 to 50 rpm, a self-rotation speed of 2000 to 4000 rpm, and a duration of 0.5 to 2 hours; for example, an orbital speed of 40 rpm, a self-rotation speed of 2700 rpm, and a duration of 1 hour.

[0070] Optionally, the process conditions for dispersing the positive electrode active material with the glue solution include: an orbital speed of 30-50 rpm, a self-rotation speed of 2000-4000 rpm, and a duration of 3-5 hours; for example, an orbital speed of 40 rpm, a self-rotation speed of 2700 rpm, and a duration of 4 hours.

[0071] The above-mentioned stirring and dispersing operations can be achieved by a high-speed stirrer.

[0072] Step S200, mixing the positive electrode slurry with the positive electrode additive to obtain a composite positive electrode slurry.

[0073] The positive electrode additive is the positive electrode additive prepared in steps S10 to S20. The amount of the positive electrode additive used can be determined according to the positive electrode material of the designed positive electrode plate. Optionally, the amount of the positive electrode additive used satisfies the formula: 0.001≤x / (η*a)≤300; wherein x is the mass fraction of the positive electrode additive to the total amount of the positive electrode material on the current collector, η is the porosity of the positive electrode plate, and a is the lithium salt concentration in the electrolyte of the lithium-ion battery used in the positive electrode plate, in mol / L. It should be understood that the total amount of positive electrode material on the current collector refers to the total mass of the positive electrode material layer on the current collector after the positive electrode plate is manufactured (or designed), and the positive electrode material may include positive electrode active materials, binders, conductive agents and positive electrode additives.

[0074] Optionally, the positive electrode slurry and the positive electrode additive are stirred and mixed at a low speed; optionally, the positive electrode slurry and the positive electrode additive are mixed at a revolution speed of 30 to 50 rpm. The stirring and mixing operation can be achieved using a stirrer. After the mixing is completed, the viscosity can be adjusted so that the composite positive electrode slurry has a viscosity suitable for coating.

[0075] Step S300, coating the composite positive electrode slurry on the current collector to obtain a positive electrode sheet.

[0076] After the composite positive electrode slurry is homogenized, it is coated. In the embodiment of the present application, the production of the positive electrode sheet is consistent with the positive electrode compaction design in the prior art. After the positive electrode sheet is coated, it is rolled, and after the rolling is completed, it is striped and die-cut.

[0077] The positive electrode sheet provided in the embodiment of the present application is prepared by the above-mentioned preparation method. After the positive electrode sheet is manufactured, the sheets are stacked and loaded into a battery housing (such as a square aluminum shell), and then the electrolyte is injected to obtain a lithium-ion battery. After the lithium-ion battery is manufactured, the capacity is divided and the K value is measured.

[0078] The characteristics and performance of the lithium-ion battery of the embodiment of the present application are further described in detail below in combination with Examples 1 to 6 and Comparative Examples 1 to 6.

[0079] Example 1

[0080] The positive electrode material on the positive electrode sheet includes positive electrode active material (lithium manganese oxide), positive electrode additive, conductive agent and PVDF, in which the positive electrode active material accounts for 95.8wt.%, and the positive electrode additive accounts for 0.2%. The injection coefficient is 3.7.

[0081] Example 2

[0082] The positive electrode material on the positive electrode sheet includes positive electrode active material (40wt.% lithium manganese oxide and 60wt.% lithium manganese iron phosphate), positive electrode additive, conductive agent and PVDF, in which the positive electrode active material accounts for 95.8wt.%, the positive electrode additive accounts for 0.2wt.%, and the injection coefficient is 3.7.

[0083] Example 3

[0084] The positive electrode material on the positive electrode sheet includes positive electrode active material (40wt.% lithium manganese oxide and 60wt.% lithium manganese iron phosphate), positive electrode additive, conductive agent and PVDF, in which the positive electrode active material accounts for 95wt.%, and the positive electrode additive accounts for 1wt.%, and the injection coefficient is 3.7.

[0085] Example 4

[0086] The positive electrode material on the positive electrode plate includes positive electrode active material (50wt.% lithium manganese oxide + 30wt.% lithium iron manganese phosphate + 20wt.% lithium-rich manganese), positive electrode additives, conductive agent and PVDF. Among the positive electrode materials, the positive electrode active material accounts for 95wt.%, and the positive electrode additive accounts for 1wt.%. The injection coefficient is 3.7.

[0087] Example 5

[0088] The injection coefficient is 2.5, and other process parameters are the same as those in Example 2.

[0089] Example 6

[0090] The injection coefficient is 4.5, and other process parameters are the same as those in Example 2.

[0091] Comparative Example 1

[0092] Compared with Example 1, no positive electrode additive is added, the proportion of positive electrode active material in the positive electrode material is 96wt.%, and the other process parameters are the same as those in Example 1.

[0093] Comparative Example 2

[0094] Compared with Example 2, no positive electrode additive is added, the proportion of positive electrode active material in the positive electrode material is 96wt.%, and the other process parameters are the same as those in Example 2.

[0095] Comparative Example 3

[0096] Compared with Example 3, no positive electrode additive is added, the proportion of positive electrode active material in the positive electrode material is 96 wt.%, and the other process parameters are the same as those in Example 3.

[0097] Comparative Example 4

[0098] Compared with Example 4, no positive electrode additive is added, the proportion of positive electrode active material in the positive electrode material is 96 wt.%, and the other process parameters are the same as those in Example 4.

[0099] Comparative Example 5

[0100] Compared with Example 5, no positive electrode additive is added, the proportion of positive electrode active material in the positive electrode material is 96 wt.%, and the other process parameters are the same as those in Example 5.

[0101] Comparative Example 6

[0102] Compared with Example 6, no positive electrode additive is added, the proportion of positive electrode active material in the positive electrode material is 96 wt.%, and the other process parameters are the same as those in Example 6.

[0103] Table 1 shows the performance test structure of the lithium ion batteries of Examples 1 to 6 and Comparative Examples 1 to 6 of the present application.

[0104] Table 1:

[0105]

[0106]

[0107] As can be seen from Table 1, after adding the positive electrode additive provided by the embodiment of the present application to the positive electrode sheet, the cycle performance and storage performance of the lithium-ion battery can be significantly improved. The positive electrode additive has a good liquid absorption capacity, which can improve the liquid retention of the positive electrode sheet and significantly reduce the liquid injection coefficient. The positive electrode additive can be coated on the surface of lithium iron manganese phosphate and lithium manganese oxide, reducing the side reactions of the positive electrode material and the electrolyte. The addition of the positive electrode additive enhances the wetting effect of the positive electrode sheet, better activates the positive electrode material, improves the capacity of the positive electrode, improves the interface uniformity of charge and discharge, and improves the cycle performance and shelf performance.

[0108] In summary, the preparation method of the positive electrode additive provided in the embodiment of the present application includes: obtaining polymer organic acid particles; using an esterification reaction to react the surface of the polymer organic acid particles to form an ester shell to obtain a positive electrode additive with a core-shell structure. In the positive electrode additive with a core-shell structure, the core of the polymer organic acid can play a better liquid absorption function, and the lipid shell has a better liquid retention function. Used as a functional additive, the positive electrode additive can form a polymer network in the positive electrode plate. The polymer has a highly swellable physical property. It absorbs electrolyte in a liquid-rich state and releases electrolyte in a liquid-poor state. Its main function is to significantly improve the wetting effect of the positive electrode plate, improve the battery capacity, improve the interface, and improve the cycle performance. Moreover, while improving the performance, it can significantly reduce the injection coefficient of the lithium-ion battery.

[0109] The positive electrode additive provided in the embodiment of the present application is prepared by the above preparation method. The positive electrode plate and its preparation method, and lithium ion battery provided in the embodiment of the present application all use the above positive electrode additive, so the obtained positive electrode plate and lithium ion battery have better performance.

[0110] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a positive electrode additive for preparing a positive electrode additive for a lithium ion battery, characterized in that: The preparation method of the positive electrode additive comprises: Obtaining high molecular weight organic acid particles; The surface layer of the polymer organic acid particles is reacted by esterification reaction to form an ester shell, so as to obtain a positive electrode additive with a core-shell structure.

2. The method for preparing the positive electrode additive according to claim 1, characterized in that: The steps of obtaining high molecular weight organic acid particles include: Using an initial organic acid to obtain a high molecular weight organic acid through a polymerization reaction; The polymer organic acid is granulated to obtain the polymer organic acid particles.

3. The method for preparing the positive electrode additive according to claim 2, characterized in that: The structural formula of the initial organic acid is The structural formula of the polymer organic acid is Wherein, R1 is an unsaturated alkenyl or alkynyl group, and the number of carbon atoms is 2 to 5.

4. The method for preparing the positive electrode additive according to claim 1, characterized in that: The particle size of the polymer organic acid particles is 0.001 to 3 μm.

5. The method for preparing the positive electrode additive according to claim 1, characterized in that: The step of using an esterification reaction to react the surface layer of the polymer organic acid particles to form an ester shell to obtain a positive electrode additive with a core-shell structure comprises: The polymer organic acid particles are placed in an alcohol solution, and the surface layer of the polymer organic acid particles is reacted under the catalysis of an inorganic catalyst to form the ester shell, so as to obtain the positive electrode additive with a core-shell structure.

6. The method for preparing the positive electrode additive according to claim 5, characterized in that: The structural formula of the alcohol solution is Wherein, R2 is a substituted or unsubstituted alkyl group containing 1 to 5 carbon atoms, or a substituted or unsubstituted alkenyl group containing 2 to 5 carbon atoms, or a functional group containing 5 carbon atoms and the substituent is F or F-containing.

7. A positive electrode additive, characterized in that: The positive electrode additive is prepared by the preparation method of any one of claims 1 to 6.

8. A method for preparing a positive electrode sheet, characterized in that: include: Obtaining a positive electrode slurry containing a positive electrode active material; Mixing the positive electrode slurry with the positive electrode additive according to claim 7 to obtain a composite positive electrode slurry; The composite positive electrode slurry is coated on a current collector to obtain a positive electrode sheet.

9. The method for preparing a positive electrode sheet according to claim 8, characterized in that: The positive electrode active material is selected from at least one of lithium manganese oxide, lithium iron manganese phosphate and nickel-cobalt-manganese ternary material.

10. The method for preparing a positive electrode sheet according to claim 8, characterized in that: The step of obtaining a positive electrode slurry containing a positive electrode active material comprises: Mixing polyvinylidene fluoride and N-methylpyrrolidone, and stirring evenly to obtain a glue solution; Dispersing the conductive agent evenly in the glue solution; The positive electrode active material is uniformly dispersed in the glue solution to obtain the positive electrode slurry.

11. The method for preparing a positive electrode sheet according to claim 10, characterized in that: The process conditions for stirring to obtain the glue solution include: a revolution speed of 30 to 50 rpm, a rotation speed of 2000 to 4000 rpm, and a duration of 1 to 3 hours; The process conditions for dispersing the conductive agent in the glue solution include: a revolution speed of 30 to 50 rpm, a rotation speed of 2000 to 4000 rpm, and a duration of 0.5 to 2 hours; The process conditions for dispersing the positive electrode active material with the glue solution include: a revolution speed of 30 to 50 rpm, a rotation speed of 2000 to 4000 rpm, and a duration of 3 to 5 hours.

12. The method for preparing a positive electrode sheet according to claim 8, characterized in that: The positive electrode slurry and the positive electrode additive are mixed at a revolution speed of 30 to 50 rpm.

13. The method for preparing a positive electrode sheet according to claim 8, characterized in that: The usage amount of the positive electrode additive satisfies the formula: 0.001≤x / (η*a)≤300; wherein x is the mass fraction of the positive electrode additive to the total amount of positive electrode material on the current collector, η is the porosity of the positive electrode plate, and a is the lithium salt concentration in the electrolyte of the lithium ion battery used for the positive electrode plate, in mol / L.

14. A positive electrode sheet, characterized in that: The positive electrode sheet is prepared by the preparation method of any one of claims 8 to 13.

15. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 14.